2015
DOI: 10.1093/annonc/mdv011
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab continuation versus no continuation after first-line chemotherapy plus bevacizumab in patients with metastatic colorectal cancer: a randomized phase III non-inferiority trial (SAKK 41/06)

Abstract: ClinicalTrials.gov, number NCT00544700.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 15 publications
0
71
0
4
Order By: Relevance
“…19). 7 Furthermore, anti-VEGF does not prolong disease-free survival (DFS) when added to adjuvant chemotherapy in patients with stage III colon cancer, and the DFS HR for anti-VEGF combined with folinic acid/ fluorouracil/ Oxaliplatin (FOLFOX4) versus FOLFOX4 was 1.17 (95% CI: 0.98-1.39; P=0.07). 8 A previous study has shown that anti-angiogenic therapy may have the unintended effect of increasing tumor invasiveness and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…19). 7 Furthermore, anti-VEGF does not prolong disease-free survival (DFS) when added to adjuvant chemotherapy in patients with stage III colon cancer, and the DFS HR for anti-VEGF combined with folinic acid/ fluorouracil/ Oxaliplatin (FOLFOX4) versus FOLFOX4 was 1.17 (95% CI: 0.98-1.39; P=0.07). 8 A previous study has shown that anti-angiogenic therapy may have the unintended effect of increasing tumor invasiveness and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In the phase Ⅲ, non-inferiority SAKK 41/06 study in which patients received 4~6 months of bevacizumab in combination with chemotherapy as first-line treatment, the time-toprogression (TTP) of a bevacizumab maintenance therapy group was compared with an observation group. In the bevacizumab maintenance therapy group, the TTP was 4.1 months, while that in the observation group was 2.9 months, HR=0.74 (95% CI, 0.57~0.95; P=0.47), which failed to reach the preset HR value of 0.727 (Koeberle et al, 2013). Overall, these prospective phase Ⅲ studies indirectly suggest that sustained bevacizumab exposure can produce a greater survival benefit.…”
Section: Figure 1 Impact Of Duration Of Bevacizumab Administration Amentioning
confidence: 89%
“…[10][11][12]14,15,[17][18][19] Of these, 5 trials were selected for additional analysis, because these trials evaluated a separately defined "maintenance phase," with randomization after the induction phase ( . The selected studies were assessed for potential bias with regard to the randomization approach, timely parallel enrollment, similarity of treatment groups, data-driven reporting, analysis population (intent-to-treat [ITT] vs. other), and other aspects.…”
Section: Definition Of Analysis and Trial Selectionmentioning
confidence: 99%
“…[13][14][15] Furthermore, the heterogeneities in the trial design (superiority in CAIRO3 and noninferiority in AIO KRK 0207 and SAKK 41/06), patient inclusion criteria (eg, exclusion of patients with toxic effects from induction treatment in CAIRO3), and the treatment applied (eg, differences in induction treatment and fluoropyrimidine maintenance schedule) should be considered as potential biases. The induction treatment was heterogeneous among the trials in terms of duration, ranging from 4 to 6 months, the use of oxaliplatin (100% of patients in CAIRO3 and AIO KRK 0207, 62% in SAKK 41/06, with 31% receiving irinotecan), intensity (7% received induction treatment with fluoropyrimidine and bevacizumab in the SAKK 41/ 06), and the fluoropyrimidine backbone used (capecitabine/oxaliplatin at 100% in CAIRO3 and only 16% in AIO KRK 0207).…”
Section: Alexander Stein Et Almentioning
confidence: 99%
See 1 more Smart Citation